INTERNATIONAL SOCIETY FOR KRISHNA CONSCIOUSNESS AS A PARTICIPANT IN СULTURAL GLOBALIZATION - T. V. Yasnaya (Концепт: философия, религия, культура, 2019)
During the 19th-20th centuries Gaudi-Vaishnavism was undergoing transformation within the reformist Hindu movement, acquiring the features of universalism and going beyond the bounds of ethnicity. This process was provided by its ideological basis termed bhakti cult, accepting people of any race, gender and social status. Due to a vast missionary activity the members of Russian Society for Krishna Consciousness (RSKCON) created a “Vedic” subculture in Russia covering more than one hundred thousand Russians. This phenomenon brings together the followers of “Slavic Vedism”, Hinduism and New Age movements.However, this does not indicate that gaudia-vaishnavism integration into the Russian society has succeeded. The information broadcast under the marker of “Vedic knowledge” turns out to be disconnected from its ideological source, and is more often perceived by the Russians out of Krishnaism. In addition, there appeared the reverse side of this mass subculture which is a large-scale criticism of “vedism” proceeding from disenchantment of people, facing deception and extortion of money under the guise of pious donations, mental and even physical violence.Despite all the efforts of The International Society for Krishna Consciousness (ISCKON) to integrate into the Russian society, this process has not yet been completed. Uncompromising religious principles, exotic cult practices, internal conflicts, distance from the society, as well as an intense activity of anti-cult associations prevent the Society from competing with mainstream denominations in Russia. At the same time, it can be argued that the ISCKON promoted a new cultural formation in the Russian society at the interface between Hinduism and the New Age movement.